(untitled) (International Conference on Computers in Education, 2016)
We have developed a learning environment for problem-posing as sentence integration. In this exercise, a learner is required to select and arrange given simple sentence cards for posing problems. On the other hands, learners write problems from scratch in usual problem-posing. Because it is very difficult for learners with reading disability to write a sentence, they cannot exercise by usual problem-posing virtually even though a teacher would like to teach the arithmetic word problems to them through problem-posing exercise. However, several learners with reading disability are able to read a simple sentence. So, we assumed that these learners realize to exercise problem-posing by problem-posing as sentence integration. Moreover, its practical use targeted as sixteen junior high school students in special classroom is reported.